Genome-wide identification and functional characterization of the two-component system gene family in petunia reveals roles in hormone signaling and stress response - Dai, Binbin; Huo, Juntao; Zhang, Linxia; Zou, Peishan; Sun, Miaomiao; Dai, Seping; Liu, Guofeng (Frontiers in Plant Science, 2025)
The two-component system (TCS) regulates key processes in plant growth, development, and stress response. Although TCS genes have been studied in model plants such as Arabidopsis and tomato, in petunia (Petunia axillaris), a model ornamental species, they remain poorly characterized at the genome-wide level. This study aimed to perform a comprehensive genome-wide analysis of TCS genes in petunia and investigate their expression patterns in response to hormones and abiotic stresses. A total of 74 TCS genes were identified, comprising 24 histidine kinases/histidine kinase-like (HK(L)s), 10 histidine phosphotransfers (HPs), and 40 response regulators (RRs). Comprehensive analyses of gene structures, conserved domains, and phylogenetic relationships suggested potential evolutionary divergence and functional specialization within TCS gene families. Tissue-specific expression profiles obtained via qRT-PCR revealed higher expression of TCS genes in leaves and roots. Analysis of cis-regulatory elements (CREs) indicated an enrichment of hormone- and stress-responsive motifs in petunia TCS promoters, with the abscisic acid (ABA)-responsive element (ABRE) being the most abundant, found in 63 genes, followed by the anaerobic response (ARE) and stress response (STRE) elements. We further analyzed response patterns to exogenous hormones (trans-zeatin (tZ) and ABA) and abiotic stresses (drought and salinity) using qRT-PCR. Compared to untreated controls, many TCS genes exhibited statistically significant up- and down-regulation (|log2FC| > 1, p < 0.05). These findings provide new insights into the regulatory roles of TCS genes in Petunia and identify candidate regulators for functional validation and molecular breeding to improve the floral traits and stress tolerance of ornamental plants.